2011
DOI: 10.1007/s10682-011-9534-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of macropters during range expansion of a wing-dimorphic insect species

Abstract: Marked changes in distribution in consequence of global warming have been observed not only for highly mobile insect taxa, which are capable of flight, but also for wing-dimorphic species with predominantly short-winged individuals. In the special case of wing-dimorphic species, it is likely that the rarer long-winged (macropterous) morph plays an important role in the dispersal process, but little is known about how and to what extent it is involved. The aim of our study was to provide more information on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…roeselii and C . discolor : multiple studies suggest both species are expanding their ranges successfully through a combination of effective dispersal (aided by high numbers of macropterous individuals) and subsequent high reproductive rates (of brachypters); selection for increased dispersal at the advancing range margin appears to be reinforcing the process [ 18 , 19 , 40 , 80 , 91 , 92 ]. Wing-length is not identified as a significant predictor of range change in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…roeselii and C . discolor : multiple studies suggest both species are expanding their ranges successfully through a combination of effective dispersal (aided by high numbers of macropterous individuals) and subsequent high reproductive rates (of brachypters); selection for increased dispersal at the advancing range margin appears to be reinforcing the process [ 18 , 19 , 40 , 80 , 91 , 92 ]. Wing-length is not identified as a significant predictor of range change in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While brachypters are limited in dispersal ability, macropters are able to Cwynar & MacDonald (1987) engage in strong pulses of long-distance range expansion under favorable environmental conditions (Hochkirch & Damerau, 2009). Multiple studies have reported higher proportions of macropterous individuals at recently colonized range fronts, suggesting that these dispersal-oriented morphs may act as the initial Morphology Achene size Bartle et al (2013) colonists prior to population establishment [crickets (Thomas et al, 2001;Simmons & Thomas, 2004;Poniatowski et al, 2012) and beetles (Niemela & Spence, 1991, 1999]. Not only can the frequency of dispersal morphs differ across an expanding range, but the dispersal ability of macropterous individuals may be elevated at the margins.…”
Section: Morphologymentioning
confidence: 99%
“…This experimental study was conducted to simulate the evolution of dispersal traits at invasion fronts, and revealed that variability of the measured traits was also increased in these individuals. In wing-dimorphic insects, range shifting is also associated with an increase of the dispersal capacities of the macropterous individuals from expansion range margins [181]. Moreover, the higher occurrence of macropters of the cricket Metrioptera roeselii in recently colonized areas reveals the crucial role played of this insect morph during range expansion [181].…”
Section: Range Expansion and Evolution Of Insect Dispersal Traitsmentioning
confidence: 99%